2003
DOI: 10.1038/sj.thj.6200306
|View full text |Cite
|
Sign up to set email alerts
|

Role of coagulation testing in predicting bleeding risk

Abstract: Coagulation testing is employed widely prior to open surgery and invasive procedures. This is based on the assumption that such testing is of clinical value in the prediction of bleeding. In order to improve the clinical understanding of the potential limitations of first-line coagulation tests used in this way, we have systematically reviewed the literature that addresses the value of routine coagulation testing in helping to predict bleeding risk. We conclude unreservedly that indiscriminate coagulation test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 31 publications
0
70
0
3
Order By: Relevance
“…As no questionnaire on bleeding diathesis has been validated for the preoperative period, many anesthesiologists and other physicians still prescribe nonspecific coagulation tests (PT, aPTT, platelet count) for reassurance. Nevertheless, a number of reviews 2,3 have shown both limited sensitivity and specificity of these tests. Given the low prevalence of bleeding disorders, ordering routine coagulation tests results on the one hand in a high number of false positives that leads to further unnecessary examinations, and on the other hand in numerous false negatives which lead to false reassurance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As no questionnaire on bleeding diathesis has been validated for the preoperative period, many anesthesiologists and other physicians still prescribe nonspecific coagulation tests (PT, aPTT, platelet count) for reassurance. Nevertheless, a number of reviews 2,3 have shown both limited sensitivity and specificity of these tests. Given the low prevalence of bleeding disorders, ordering routine coagulation tests results on the one hand in a high number of false positives that leads to further unnecessary examinations, and on the other hand in numerous false negatives which lead to false reassurance.…”
Section: Discussionmentioning
confidence: 99%
“…Indiscriminate coagulation tests are still widely ordered prior to surgery, although these have limited sensitivity and specificity as well as poor positive and negative predictive values for bleeding. [2][3][4] Over the last decade, various anesthesiology and hematology societies have published guidelines regarding preoperative hemostatic evaluation. [5][6][7] These recommend that, prior to invasive procedures, the risk of bleeding should be assessed using personal and family bleeding histories in addition to a physical examination.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been several attempts to debunk this myth. [6][7][8][9] These reports stress the fact that a good history from the patient or family, or their records, is most important in predicting bleeding risk. Anyone who has bled excessively after surgery or a dental extraction in the past is more likely to have a bleeding disorder.…”
Section: Prolonged Pt and Aptt Predict The Risk Of Bleedingmentioning
confidence: 99%
“…7 Hayward et al explored the use of PT and APTT among individuals referred for bleeding disorder assessments, using data from a bleeding disorder study to determine sensitivities and specifi cities. They identifi ed that coagulation defects were uncommon and the APTT detected many non-signifi cant abnormalities.…”
Section: Prolonged Pt and Aptt Predict The Risk Of Bleedingmentioning
confidence: 99%